A 10-year delayed diagnosis of blue rubber bleb nevus syndrome characterized by refractory iron-deficiency anemia: A case report and literature review. Issue 22 (June 2018) - Tang, Xue; Gao, Ju; Yang, Xue; Guo, Xia
Abstract: Rationale: Blue rubber bleb nevus syndrome (BRBNS) is a rare vascular disorder consisting of multifocal venous malformations. Delayed diagnosis or misdiagnosis frequently occurs in patients without typical cutaneous lesions or gastrointestinal bleeding symptoms. This article reports a 10-year case of delayed diagnosis of BRBNS detected by capsule endoscopy. Patient concerns and diagnosis: A 15-year-old girl presented with refractory iron-deficiency anemia (IDA) for 10 years, without any hemorrhagic signs or noticeable cutaneous lesions, which led to her obvious physical growth retardation. Capsule endoscopic examination revealed dozens of vascular blebs distributed from the jejunum to the ileum and a site of active bleeding. Hence, she was diagnosed with BRBNS. Interventions: Laparotomy was performed with resection of the small bowel lesions, and iron supplementation was prescribed for 3 months. Postoperatively, the patient had an uncomplicated course. Outcomes: On follow-up after 3 years, IDA in this patient was cured and she did not require further blood transfusion and showed excellent vigor. Lessons: A high index of suspicion for BRBNS and adequate endoscopy examination will help to identify the origin of refractory IDA in older children, particularly in patients with vascular lesions of the skin.